The impact of the economic crisis on media framing: evidence from three elections in Ireland. (22nd October 2013) - O'Malley, Eoin; Brandenburg, Heinz; Flynn, Roddy; McMenamin, Iain; Rafter, Kevin
Abstract : Media coverage of elections in Europe and North America has increasingly focused on the campaign as a game rather than a policy debate. This is often explained by the changes in media pressures. It may also reflect the narrowing of policy space between left and right and the comparative prosperity enjoyed in Europe and North America. But the relevance of policy varies. The global economic crisis might have led to an increased interest in policy among voters and focus on it by media. Ireland experienced both extremes of boom and crisis between the late 1990s and 2011. The Irish case allows us to test the impact of the crisis on media framing of elections. This article uses original data from the three most recent national elections in Ireland, with a research design that holds other pertinent variables constant. We find empirical support for the theoretical expectation that the context of the election affects the relative focus on campaign or horserace vs. substantive policy issues.